The role of mediating effect of emotional intelligence on the relationship between job satisfaction and job preferences - Ameneh MOAZEDIAN; Zahra PEZESHKI; Elahe KAZEMI (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Introductin: A large portion of a person's days is spent at work. Job satisfaction has an important role in deliverables quality and goal achieved. Job satisfaction affects job interest and emotional intelligence so that, a study was conducted in 2018 in the Ministry of Health and Medical Education to determine the mediating effect of emotional intelligence on the structural relationship between job satisfaction and job interest among 253 Ministry of Health and Medical Education experts. Method: Evaluation was based on the Amabile's, two-factor Herzberg's and Golman's theories using the Amabile work preference, Danet job satisfaction, and sharing emotional intelligence questionnaires. Research was conducted by available sampling method. The research was a cross-sectional and descriptive and correlational. In order to test the hypotheses, the path analysis method in the structural equations model in AMOS software was used. The Sobel test was used to examine the mediating effect of emotional intelligence as intermediate variable. Results: The results indicated that there was a significant and positive relationship between intrinsic and extrinsic motivations of job preferences, emotional intelligence, and job satisfaction based on the direct effect coefficient. Conclusion: In conclusion, the direct and indirect effects of the mediation variable and predicted variable shows that emotional intelligence has the most effects on job satisfaction and, the internal instinct is in the second place. Based on the study, emotional intelligence is a mediation variable between job preferences and job satisfaction.